2005
DOI: 10.1111/j.1468-2982.2005.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Cephalic Jabs (?) The Vågå Study of Headache Epidemiology

Abstract: Jabs (stabs) usually last < or = 3 s and are located in the skull area, mostly anteriorly. In many cases, there are only a few jabs during lifetime. With this definition, jabs are frequent, thus at 35.2% in the Vågå study of headache epidemiology. Long-lasting jabs (?), i.e. paroxysms lasting 10-120 s, were present in six out of 1779 parishioners. These pain paroxysms seemed mainly to be side-locked, but could not be provoked. Possibly, these long-lasting jabs after all mainly are regular jabs. To include the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
(68 reference statements)
3
14
0
2
Order By: Relevance
“…A peculiar feature was that during these short-lasting paroxysms, dizziness overshadowed the pain part. There were, however, no visual disturbances/disturbances of depth vision, ocular pain or nausea, as described elsewhere, and the jabs were never protracted [29]. Usually, these episodes were non-synchronous with M-A.…”
Section: A Particular Case With Marked Allodyniamentioning
confidence: 98%
See 1 more Smart Citation
“…A peculiar feature was that during these short-lasting paroxysms, dizziness overshadowed the pain part. There were, however, no visual disturbances/disturbances of depth vision, ocular pain or nausea, as described elsewhere, and the jabs were never protracted [29]. Usually, these episodes were non-synchronous with M-A.…”
Section: A Particular Case With Marked Allodyniamentioning
confidence: 98%
“…Prolonged jabs (? ), i.e., jabs with a duration up to 120 s, have been dealt with separately [29]. The present group makes up <1% of jabs in Vågå, where jabs were found in 35.2% of the population.…”
Section: Cph: a Comment On Its Diagnosismentioning
confidence: 99%
“…Nevertheless, long-lasting cephalic jabs had been reported [27]. Clinic-based studies showed PSH occurred more often in migraineurs [5, 6, 15••].…”
Section: Primary Stabbing Headachementioning
confidence: 99%
“…Interessanterweise scheint auch ein anderes, akut beginnendes, im Zeitverlauf nur deutlich kürzeres Kopfschmerzsyndrom mit heftigen Attacken eine Verbindung zur Migräne zu haben, das Jabs-and-Jolts-Syndrom bzw. "longlasting cephalic jabs" [13]. Pathophysiologisch wird eine akute neuronale Entladung im trigeminalen System diskutiert [13].…”
Section: Diskussionunclassified
“…"longlasting cephalic jabs" [13]. Pathophysiologisch wird eine akute neuronale Entladung im trigeminalen System diskutiert [13]. Die Migräne führt neben einer kurzen initialen Hyperämie zu einer dann länger anhaltenden Oligoämie, was als Folge einer kortikalen Spreading-Depression angesehen wird [2], wobei diese Prozesse auch subakut beginnen können, wie akute Auren, z.B.…”
Section: Diskussionunclassified